Technology and Community Based Zakat, Infaq, and Sodaqah Fundraising Model - Khabib Solihin; Umi Latifah (NUsantara Islamic Economic Journal, 2022)
Fundraising has a strategic role in the success of LAZIS in providing benefits to the people, this role has at least three forms, namely first, the fundraising strategy is the need to improve organizational governance, the second is the fundraising strategy is one of the means for institutional strengthening; the three fundraising strategies must take advantage of the opportunities and challenges in the digital era by changing digital fundraising technology. These three aspects indicate that fundraising is one aspect that affects the success of a ZIS Management Institution. Fundrising is one of the basic needs that cannot be ruled out. Development and innovation in the funding strategy must always be carried out in order to achieve an effective and efficient strategy. The development of technology as the main capital at this time and the emergence of various communities in society which contain large social capital must be collaborated with conventional fundrising models so that they can improve the performance of the ZIS Management Institution in collecting ZIS in the current era. Therefore, the development of fundrising strategies that utilize technology such as QR Codes, websites, zakat calculators, ZIS applications should also be pursued to facilitate and provide effectiveness in tithing. Not only that, the use of the community in which social capital is stored is also important to note. Didi Kempot with his charity concert which empowers the community of friends ambyar and wrapped with the latest technology has proven to be effective in raising funds. Therefore, a fundrising model using technology and the community needs to be developed for a more optimal, effective, and efficient ZIS fundraising